STRATEGIC INFRASTRUCTURE DEVELOPMENT: DRIVING ECONOMIC PROSPERITY AND JOB CREATION - Ben Brahim S. B.; Sidderatul Akbar; Oggy Akmadani (CV. Adiba Aisha Amira, 2024)
Strategic infrastructure development is a key component in driving economic growth and creating jobs in a country. Infrastructure such as roads, harbours, airports and telecommunication networks not only facilitate the movement of goods and services, but also attract investment and encourage the development of various economic sectors. In addition, the process of infrastructure development itself creates direct and indirect employment. However, the success of infrastructure development depends on careful planning, effective implementation and sustainable management. With the right approach, strategic infrastructure development can be a powerful catalyst for achieving economic prosperity and creating sustainable employment opportunities.